Alterations of state : sacred kingship in the English Reformation - McCoy, Richard C., 1946- (Columbia University Press, 2002)
During the English reformation, writers like John Skelton, Shakespeare, John Milton, and Andrew Marvell grappled with the idea of kingship and royalty, its real presence and figurative power. McCoy explains why religious devotion to the royal person became both more acute and more problematic during England's turbulent seventeenth century.
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism.; Kings and rulers in literature.; Christianity and literature -- Great Britain -- History -- 16th century.; Christianity and literature -- Great Britain -- History -- 17th century.; Kings and rulers -- Religious aspects -- Christianity.; Politics and literature -- Great Britain -- History.; Church and state in literature.; State, The, in literature.; Holy, The, in literature.; Monarchy in literature.; Politics and literature -- Great Britain -- History -- 16th century.; Politics and literature -- Great Britain -- History -- 17th century.; Rois et souverains -- Aspect religieux -- Christianisme.; Rois et souverains dans la littérature.; Christianisme et littérature -- Grande-Bretagne -- Histoire -- 16e siècle.; Christianisme et littérature -- Grande-Bretagne -- Histoire -- 17e siècle.; Politique et littérature -- Grande-Bretagne -- Histoire -- 16e siècle.; Politique et littérature -- Grande-Bretagne -- Histoire -- 17e siècle.; Sacré dans la littérature.; État dans la littérature.; Église et État dans la littérature.; Politique et littérature -- Grande-Bretagne -- Histoire.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; HISTORY -- Europe -- Great Britain.; Christianity and literature; Church and state in literature; English literature -- Early modern; Holy, The, in literature; Kings and rulers in literature; Kings and rulers -- Religious aspects -- Christianity; Monarchy in literature; Politics and literature; State, The, in literature; Great Britain; Reformatie.; Koningschap.; Het Heilige.; Engeland.; 1500-1700; Criticism, interpretation, etc.; History